A Critical Analysis of Judicial Discretion of Granting Bail in India: Examining the Impact of Judicial Discretion on Bail Granting in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Pre-trial incarceration has exceptionally harsh and merciless repercussions, making anaccused person's right to be released on bail critical. If the accessed person's right to bail is refused, hewill be exposed to the mental and physical anguish of jail life even though he is deemed innocent untilhis guilt is proven beyond a reasonable doubt. The Criminal Procedure Code (hence referred to as thecode) of 1973 made posting bail a mandatory step. The accused individual holds this as one of his or hermost prized rights, claims, or advantages. There are two contradictory demands in the rules of bail, oneof which is the need for society to be protected from an accused person's potential mishaps, and theother is the presumption of innocence until the accused is proven guilty. The, Bail provisions combinesthe goals of justice and individual freedom. According to the 1973 Criminal Procedure Code, there is nodefinition of bail.